Talking Stick Learning Model Test on Biology Students Cognitive Learning Outcomes - Purba, Ika Rosenta (International Journal of Educational Research & Social Sciences, 2021)
The talking stick learning model is a learning model that allows students to be active and creative so that Students cognitive learning outcomes can be achieved. This learning model basically uses the help of a stick, but in practice it can be combined with appropriate learning media. In this case, the researcher only used the stick as a test of the talking stick learning model on Studentscognitive learning outcomes. The method of testing this model used a quasi-experimental design with a One-group pretest-posttest design with 3 trials. The results of the research proved that the second (71.56) and third (78.44) experiments have reached the KKM (> 70). This proves that the talking stick learning model can improve Students cognitive biology learning outcomes.